G6PD genetic variations in neonatal Hyperbilirubinemia in Indonesian Deutromalay population - Dewi A. Wisnumurti; Yunia Sribudiani; Robert M. Porsch; Ani M. Maskoen; Sri E. Rahayuningsih; Eni K. Asni; Frank Sleutels; Wilfred F. J. van Ijcken; Abdurachman Sukadi; Tri H. Achmad (BMC, 2019)
Abstract Background Neonatal jaundice is a common finding in newborns in Asia, including Indonesia. In some cases, the serum total bilirubin levels exceeds the 95th percentile for hours of life (neonatal hyperbilirubinemia). Severe neonatal hyperbilirubinemia (NH) could lead to kernicterus and neonatal death. Glucose-6-Phosphage Dehydrogenase (G6PD) genetic variations and deficiency have been reported in several studies to be associated with NH. This study aimed to analyze the G6PD genetic variations and its activity in neonates with and without hyperbilirubinemia in the Deutromalay Indonesian population. Methods Deoxyribose Nucleic Acid (DNA) was isolated from peripheral blood of 116 and 115 healthy term neonates with and without hyperbilirubinemia. All infants underwent the following laboratory examinations: routine hematologic evaluation, Coombs test, G6PD activity measurement using the Randox kit method, and serum total bilirubin level. All exons of the G6PD gene were targeted for deep sequencing using MiSeq (Illumina). An association study of G6PD polymorphisms with NH was performed using PLINK. Results The prevalence of G6PD deficiency in neonates with and without hyperbilirubinemia in Indonesian Deutromalay population were 1.72% (95% Confidence Interval (CI): 0.6-4.1%) and 1.74% (95% CI: 0.7-4.1%), respectively. The most common G6PD polymorphisms, i.e. rs1050757/c.* + 357A > G, rs2230037/c.1311C > T, and rs2071429/c.1365-13 T/IVS11, were identified. However, none of those polymorphisms and their haplotype were associated with NH (p > 0.05, Odds Ratio (OR) ~1.00). The prevalence of G6PD mutations in neonates with and without hyperbilirubinemia were 6.8% (95% CI: 2.3-11.5%) and 6.9% (95% CI: 2.3-11.6%), respectively. The most frequently identified G6PD mutation was the Viangchan variant (p.V291 M), which was followed by the Canton (p.R459L) and Vanua Lava (p.L128P) variants. Two novel mutations were identified both in case (p.V369A, p.I167F) and control (p.L474=, p.I36T) groups. Conclusion The prevalence of G6PD deficiency is low in neonates with or without hyperbilirubinemia in Deutromalay Indonesian population. The majority of G6PD mutations identified among Indonesian Deutromalay population in this study are Viangchan, Canton and Vanua Lava variants.